Characterization of the aromatic profile of purple passion fruit (Passiflora edulis Sims) during ripening by HS-SPME-GC/MS and RNA sequencing. (1st September 2021) - Li, Changbao; Xin, Ming; Li, Li; He, Xuemei; Yi, Ping; Tang, Yayuan; Li, Jiemin; Zheng, Fengjin; Liu, Guoming; Sheng, Jinfeng; Li, Zhichun; sun, Jian
Highlights: Esters, alcohols, ketones, hydrocarbons, alkanes and aldehydes were the mainly VOCs in passion fruit. VOCs accumulated gradually, especially the change of esters is the most significant during passion fruit ripening. 'Color change stage' was key period for aroma formation in passion fruit. Ester biosynthesis pathway and genes (AAT, LOX and HPL) were identified as active during ripening. Abstract: Passion fruit is a tropical liana of the Passiflora family that is commonly consumed throughout the world due to its attractive aroma and flavor. However, very limited information is available on the mechanism of aroma formation and composition of the passion fruit during ripening. Therefore, HS-SPME-GC/MS combined with transcriptome analysis was used to study the mechanism of aroma formation during passion fruit ripening. The profile analyzed included 148 volatile organic compounds (VOCs) and related differentially expressed genes (DEGs). Compared with SA, 85 VOCs and related DEGs were identified as significantly upregulated at the SB and SC stages, including esters, alcohols, ketones, hydrocarbons, alkanes, and aldehydes. Two main pathways, ester and amino acid metabolism, and related genes were analyzed with VOC biosynthesis in passion fruit. This study is the first analysis of passion fruit VOC formation and provides new insights into the flavor mechanism and quality breeding of passion fruit.